Evaluasi Tingkat Kepuasan Mahasiswa Terhadap Kualitas Website Perpustakaan Universitas Terbuka - Hendarwati, Wira Puji; Adji, Pratiwi Anindita (Al-Ma mun Jurnal Kajian Kepustakawanan dan Informasi, 2025)
Evaluation of the level of student satisfaction with the quality of the library website is very important for a college library. This study is about the evaluation of the level of student satisfaction with the UT Library website based on user expectations and perceptions using the webqual method. The aim is to determine the extent of student satisfaction with the quality of the UT Library website based on student perceptions and expectations. The webqual method is a method used to measure website quality. The research method used is a survey, a type of quantitative research by giving questionnaires to 100 students who have accessed the library website. Data processing and data analysis techniques use SPSS for Windows version 17 with the mean difference T-test technique which is seen from the average perception, average minimum expectation, and average ideal expectation. The difference between the perception score and the minimum expectation score creates an Adequacy Gap, and the difference between the perception score and the ideal expectation score creates a Superiority Gap. The results of the study indicate that the quality of the UT Library website has been able to meet the minimum expectations of students. This means that students are apparently "quite satisfied" with the services they receive. Keywords : webqual, website quality, perception,